Estrutura e dinâmica do sistema logístico sobre trilhos: o caso da VLI - Machado, Luiz Kennedy Cruz (2016)
The infrastructure of Brazilian transportation cannot be considered an example for the country. The precarious state a some of the logistic models become serious deterrents for transporting products. It is necessary that public and private forces develop possibilities for logistic adaptations compatible with the country´s need, given that logistic companies emerge in this scenario as an alternative for these issues. Thus, the present work was conducted with the objective of analyzing the structure and dynamics of Brazilian railway logistics and evaluate the position of the VLI company within the Brazilian context under the point-of-view of the Theory of Transaction Costs. Initially, we describe the structure and dynamics of the Brazilian railway system and its main elements. Furthermore, we analyze the governance structure adopted by VLI by means of a case study, as well as its position within the context of structure and dynamics of Brazilian railway transportation, with theoretical contribution of the theory of transaction costs, contracts and forms of management. We verified that investments from the private sector in 2013 increased the production of the railway sector when compared to analysis conducted in 1997. The Union raised R$ 39,729 billion between the years of 1997 and 2013, and the accidents reduces significantly. VLI demonstrated gain with its integrated structure of ports, railways and terminals, in constant development, generating benefits, for itself and for its clients, such as processing speed, better controlling level and better relations with clients and suppliers. A few critical points, such as non -used sections and actives, difference between gauges in the routs, high investment risk for actives and, the most critical, economic instability, were highlighted. Based on the results, document analysis shows that railway concessions were positive for Brazil, and that they directly depend of partnerships with the government in order to be competitive in the market. In conclusion, the governance structure adopted by VLI reduces transaction costs for the agents involved in providing this service.